Modelling snowpack dynamics and surface energy budget in boreal and subarctic peatlands and forests ... - Nousu, Jari-Pekka; Lafaysse, Matthieu; Mazzotti, Giulia; Ala-aho, Pertti; Marttila, Hannu; Cluzet, Bertrand; Aurela, Mika; Lohila, Annalea; Kolari, Pasi; Boone, Aaron; Fructus, Mathieu; Launiainen, Samuli (Zenodo, 2023)
The snowpack has a major influence on the land surface energy budget. Accurate simulation of the snowpack energy budget is challenging due to e.g. vegetation and topography that complicate the radiation budget, and limitations in theoretical understanding of turbulent transfer in the stable boundary layer. Studies that evaluate snow, hydrology and land surface models (LSMs) against detailed observations of all surface energy components at high latitudes are scarce. In this study, we compared different configurations of SURFEX LSM model against surface energy flux, snow depth and soil temperature observations from four eddy covariance stations in Finland. The sites cover two different climate and snow conditions, representing the southern and northern subarctic zones, and the contrasting forest and peatland ecosystems typical for the boreal landscape. We tested the sensitivity of surface energy fluxes to different process parameterizations implemented in the Crocus snowpack model. In addition, we examined ...